Complications of Mesenteric Vein Thrombosis: Heterozygous Factor V Leiden Mutation Leads to Pulmonary Embolism in a Patient With Post–Bowel Resection Surgery - Hafiz Muhammad Hamza; Muhammad Muiz Malik; Ayaz Ahmed Awan; Muhammad Daoud Tariq; Mohamed Daoud; Aman Goyal (Clinical Case Reports)
ABSTRACT It is critical to recognize pulmonary embolism as soon as possible in patients who have gastrointestinal problems pre‐ and post‐surgery. Even in the absence of conventional risk factors, the Factor V Leiden mutation emphasizes the importance of a thorough thrombophilia assessment. To effectively manage and prevent thrombotic episodes, prompt anticoagulant medication and genetic screening for family members are essential.